The impact of product image, CSR and green marketing in organic food purchase intention: Mediation roles of corporate reputation - Lakkana Hengboriboon; Phaninee Naruetharadol; Chavis Ketkeaw; Nathatenee Gebsombut (Cogent Business & Management, 2022)
Recent research has focused mainly on the impact of corporate social responsibility (CSR). However, few studies have examined the impact of CSR and corporate image on organic food consumption, particularly in developing nations. This study explores the effect of corporate social responsibility on consumers' intention to purchase organic food in Thailand. This research paper conducts quantitative analysis using a questionnaire that sampled 523 Thai consumers. To examine the effects of the product image and corporate reputation for corporations that implement corporate social responsibility programs on consumer decision-making, a structural equation model is applied. The results supported that product image and corporate image/reputation were the crucial factors influencing Thai consumers' perspectives and purchase intentions. This research contributes to guiding corporations in applying the findings to build their company image and corporate social responsibility (CSR) toward enterprises. The current study demonstrates how green knowledge and environmental concerns assist firms and contribute to achieving sustainable development goals, focusing on environmental elements. Data collection and generalization to other green consumers are limitations of this study.
Keywords: 650; company image; consumers' perspective; CSR; green marketing; marketing; organic food; product image; purchase intention; social responsibility; strategy